Vitamin d supplementation induces cardiac remodeling in rats: Association with thioredoxin-interacting protein and thioredoxin - Dos Santos, Priscila Portugal [UNESP]; Rafacho, Bruna P. M. [UNESP]; Gonçalves, Andrea F. [UNESP]; Pires, Vanessa C. M. [UNESP]; Roscani, Meliza G. [UNESP]; Azevedo, Paula S. [UNESP]; Polegato, Bertha F. [UNESP]; Minicucci, Marcos F. [UNESP]; Fernandes, Ana Angélica H. [UNESP]; Tanni, Suzana E. [UNESP]; Zornoff, Leonardo A. M. [UNESP]; de Paiva, Sergio A. R. [UNESP] (Sociedade Brasileira de Cardiologia, 2021)
Background: Vitamin D (VD) has been shown to play an important role in cardiac function. However, this vitamin exerts a biphasic “dose response” curve in cardiovascular pathophysiology and may cause deleterious effects, even in non-toxic doses. VD exerts its cellular functions by binding to VD receptor. Additionally, it was identified that the thioredoxin-interacting protein (TXNIP) expression is positively regulated by VD. TXNIP modulate different cell signaling pathways that may be important for cardiac remodeling. Objective: To evaluate whether VD supplementation lead to cardiac remodeling and if TXNIP and thioredoxin (Trx) proteins are associated with the process. Methods: A total of 250 Male Wistar rats were allocated into three groups: control (C, n=21), with no VD supplementation; VD3 (n = 22) and VD10 (n=21), supplemented with 3,000 and 10,000 IU of VD/ kg of chow respectively, for two months. The groups were compared by one-way analysis of variance (ANOVA) and Holm-Sidak post hoc analysis, (variables with normal distribution), or by Kruskal-Wallis test and Dunn’s test post hoc analysis. The significance level for all tests was 5%. Results: TXNIP protein expression was higher and Trx activity was lower in VD10. The animals supplemented with VD showed increased lipid hydroperoxide and decreased superoxide dismutase and glutathione peroxidase. The protein Bcl-2 was lower in VD10. There was a decrease in fatty acid β-oxidation, tricarboxylic acid cycle and electron transport chain with shift to increase in glycolytic pathway. Conclusion: VD supplementation led to cardiac remodeling and this process may be modulated by TXNIP and Trx proteins and consequently oxidative stress. (Arq Bras Cardiol. 2021; 116(5):970-978).
Suplementação de vitamina d induz remodelação cardíaca em ratos: Associação com a proteína de interação com a tiorredoxina e a tiorredoxina
Keywords: Oxidative Stress; Rats; Thioredoxins; Ventricular Remodeling; Vitamin D